MAPPING OF NDVI INDEX BASED MANGROVE AREA AND DENSITY CHECTARENGES USING LANDSAT 8 SATELLITES IMAGES IN NORTHERN COASTAL AREA OF EAST JAVA PROVINCE, INDONESIA - Zakiyah, Umi; Gayatri, Alifia; Maharani, Patricia Dita; Mulyanto, Mulyanto; Arfiati, Diana; Loka, Widi Ayom (Directorate of Research and Community Service (DRPM), 2024)
Mangrove ecosystems are important for maintaining ecological balance in coastal areas. To monitor changes in mangrove area and density, remote sensing technology with Landsat 8 and NDVI Index was used. The research focuses on the North Coast of East Java, from 2019-2024, on the coast of Surabaya, Sidoarjo, Pasuruan, Probolinggo, and Situbondo. The purpose of this study is to analyze changes in mangrove area and density. The survey method was conducted with Landsat 8 images and in situ data in 2024. There are 5 observation station points with the determination of station points using purposive sampling technique. Accuracy test using RMSE. The area of mangroves on the coast of Surabaya, Sidoarjo and Pasuruan from 2019 to 2024 ranged from 1611.88 ha-2270.41 ha. The highest cover area was in 2024 and the lowest in 2019. Mangroves with sparse NDVI category ranged from 46640.61 ha-53284.95 ha. Moderate NDVI ranged from 4313.25 ha-6984.72 ha and dense NDVI ranged from 493.29 ha-4711.5 ha. The area of mangroves on the coast of Probolinggo and Situbondo increased from 2019-2024, which amounted to 1487.05 ha-1885.79 ha. Mangroves with sparse NDVI category have an area between 51367.12 ha-54852.64 ha. Moderate NDVI ranged from 5564.87 ha-54852.64 ha and high NDVI ranged from 668.18 ha-1585.52 ha. The results show that there are changes in the area and density of mangroves on the north coast of East Java every year. These changes need to be monitored annually to address the decline in mangrove area and density quickly and appropriately.